2015
DOI: 10.1289/ehp.1408881
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry in 5- to 9-Year-Old Greenlandic and Ukrainian Children in Relation to Prenatal Exposure to Perfluorinated Alkyl Substances

Abstract: BackgroundIn some animal studies, perfluorinated alkyl substances are suggested to induce weight gain. Human epidemiological studies investigating these associations are sparse.ObjectiveWe examined pregnancy serum concentrations of perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) and the prevalence of offspring overweight (> 1 SD) and waist-to-height ratio (WHtR) > 0.5 at 5–9 years of age.MethodsSera from 1,022 pregnant women enrolled in the INUENDO cohort (2002–2004) from Greenland and Kharkiv (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 35 publications
(48 reference statements)
9
87
0
Order By: Relevance
“…In our study, this association did not persist at age 5, which is in agreement with the findings of three previous studies that did not observe significant associations with child BMI and/or overweight risk at mid- and late- childhood (33, 36, 38). Further, two of these studies found no clear association between prenatal exposure to PFOA and childhood overweight (33, 38), while the other study showed a positive association between PFOA and the child’s BMI (36), in agreement with the positive association with overweight risk at age 5 years reported in the present study. Although the moderate to high correlations shown between PFOS and PFOA in this and other studies do not allow us to identify their relative contributions to the associations, the findings of this study may suggest that PFOS associations with obesity primarily appear in early childhood, while PFOA associations become apparent at later ages.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, this association did not persist at age 5, which is in agreement with the findings of three previous studies that did not observe significant associations with child BMI and/or overweight risk at mid- and late- childhood (33, 36, 38). Further, two of these studies found no clear association between prenatal exposure to PFOA and childhood overweight (33, 38), while the other study showed a positive association between PFOA and the child’s BMI (36), in agreement with the positive association with overweight risk at age 5 years reported in the present study. Although the moderate to high correlations shown between PFOS and PFOA in this and other studies do not allow us to identify their relative contributions to the associations, the findings of this study may suggest that PFOS associations with obesity primarily appear in early childhood, while PFOA associations become apparent at later ages.…”
Section: Discussionsupporting
confidence: 93%
“…Very few of the previous studies also accounted for OC exposures measured postnatally (23, 29). The associations of PFAS exposures with weight gain are supported by experimental studies (30, 31), but epidemiologic studies have only recently evaluated this hypothesis, with inconsistent findings (19, 3238). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pooled analysis, continuous PFOS concentration was positively associated with offspring waist-to-height ratio (RR=1.38; CI=1.05-1.82); however, in gender-stratified analyses results were statistically significant only for girls (RR=1.54; CI=1.06-2.23) and not boys (RR=1.24; CI=0.82-1.87). There were no statistically significant findings for the association of tertiles of maternal PFCs with youth waist-to-height ratios (31). Lastly, in the Cincinnati-based HOME Study, Braun and colleagues (32) evaluated associations of prenatal PFC concentrations (PFOA, PFOS, PFHxS and PFNA) with BMI, waist circumference, and percent body fat (measured by a Tanita body fat monitor) among a modestly sized sample of 8-year old children of both genders (n=204).…”
Section: Discussionmentioning
confidence: 72%
“…The investigators reported adjusted relative risk (RR (95% CI)) of offspring overweight (defined as >85 percentile for age and sex) and unfavorable offspring waist-to-height ratio (>0.5) for continuous (natural log transformed) and tertiles of PFCs between ages 5-9 years. In country-specific and in pooled analyses, neither PFOA nor PFOS was significantly associated with offspring risk of overweight (31). In the pooled analysis, continuous PFOS concentration was positively associated with offspring waist-to-height ratio (RR=1.38; CI=1.05-1.82); however, in gender-stratified analyses results were statistically significant only for girls (RR=1.54; CI=1.06-2.23) and not boys (RR=1.24; CI=0.82-1.87).…”
Section: Discussionmentioning
confidence: 72%